2020
DOI: 10.3390/w12030824
|View full text |Cite
|
Sign up to set email alerts
|

Megacity Wastewater Poured into A Nearby Basin: Looking for Sustainable Scenarios in A Case Study

Abstract: Megacity sewage creates socioeconomic dependence related to water availability in nearby areas, especially in countries with hydric stress. The present article studies the past, current, and future water balance progression of realistic scenarios from 2005 to 2050 in the Mezquital Valley, the receptor of Mexico City untreated sewage since 1886, allowing for agriculture irrigation under unsustainable conditions. The Water Evaluation and Planning System (WEAP) was used to estimate water demand and supply, and va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This research shows the same tendency found in the Mezquital Valley, a semidesert area highly threatened by climate warming and the high growth of its industry and agriculture. Researchers have recently found high water scarcity values on surface water and groundwater in climate change scenarios [43].…”
Section: Discussionmentioning
confidence: 99%
“…This research shows the same tendency found in the Mezquital Valley, a semidesert area highly threatened by climate warming and the high growth of its industry and agriculture. Researchers have recently found high water scarcity values on surface water and groundwater in climate change scenarios [43].…”
Section: Discussionmentioning
confidence: 99%
“…The food-water quality nexus in peri-urban aquacultures downstream of Bangkok, Thailand [58] Water/Soil Megacity wastewater poured into a nearby basin: looking for sustainable scenarios in a case study [15] Water/Soil…”
Section: Title Citation Fieldmentioning
confidence: 99%
“…The peri-urban landscape transformation was reported in Latin America through the rapid growth of four developing cities, Santiago de Chile, Panama City, Mexico City, and Rio de Janeiro, with different challenges [14]. In contrast, the Mezquital Valley, northwest of Mexico City, has shown strong development in the agricultural and industrial sectors, which is allowed by the megacity sewage supply [15].…”
Section: Introductionmentioning
confidence: 99%
“…The climate crisis has had a negative effect on the hydrological cycle and water resources, which have been depleted and polluted, disrupting socio-ecological systems [6]. Groundwater is increasingly vulnerable to drought and desertification scenarios [7]. However, in the face of decreasing water availability, the proper use and management of aquifers can be an alternative for sustainable water use and adaptation to climate change [8][9][10].…”
Section: Introductionmentioning
confidence: 99%